2010
DOI: 10.1007/s11605-010-1223-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sclerosing Cholangitis and Extraintestinal Manifestations in Patients with Ulcerative Colitis and Ileal Pouch–Anal Anastomosis

Abstract: An association between primary sclerosing cholangitis and chronic/severe pouchitis was found, but not with other extraintestinal manifestations. Functional results were good and alike in patients with and without primary sclerosing cholangitis. Primary sclerosing cholangitis is a risk factor for chronic pouchitis and is associated with neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…13,14 Several studies have also shown that the presence of PSC or other immune disorders is associated with poor pouch outcome. 17,18 In this report, we confirm that Ashkenazi Jewish individuals and those who have a history of smoking (either current or ex-smokers) were significantly more likely to develop inflammatory pouch complications. We did not observe any association between outcome and first-degree family history of IBD.…”
Section: Discussionsupporting
confidence: 72%
“…13,14 Several studies have also shown that the presence of PSC or other immune disorders is associated with poor pouch outcome. 17,18 In this report, we confirm that Ashkenazi Jewish individuals and those who have a history of smoking (either current or ex-smokers) were significantly more likely to develop inflammatory pouch complications. We did not observe any association between outcome and first-degree family history of IBD.…”
Section: Discussionsupporting
confidence: 72%
“…6,24,158,159 The disadvantage of IPAA in patients with PSC-UC compared to those with UC alone is the higher risk of acuteand chronic pouchitis. 160,161 …”
Section: Complicationsmentioning
confidence: 99%
“…6,7,[36][37][38] Although patients with primary sclerosing cholangitis are more likely to develop pouchitis, no other risk factors have been consistently identified as risk factors for the development of pouchitis. 39 We found an overall 30-year cumulative probability of 80% for the development of pouchitis. Most patients only experienced 1 to 2 episodes, which resolved with antibiotic therapy, and importantly, these episodes did not appear to alter the overall QoL and functional results.…”
Section: Discussionmentioning
confidence: 68%